Utilização da casca de arroz in natura e carbonizada na composição de substratos para o cultivo de Pleurotus ostreatus - Costa, Artur Fernando Poffo (2022)
Rice husk is a waste generated in large quantities in various countries, although its reuse is limited due to low nutritional quality and high silica content. Therefore, this study sought to evaluate using raw or carbonized rice husks to partially substitute eucalyptus sawdust in substrates to produce the edible mushroom Pleurotus ostreatus. The substrates were formulated with proportions of 0 to 100% of eucalyptus sawdust and raw or carbonized rice husks. P. ostreatus was grown for 90 days on the substrates to evaluate mycelial growth, fresh mass production, biological efficiency, and protein and fat content. The organoleptic quality of the mushrooms produced was evaluated by sensory analysis. The substrates’ moisture, pH, and C and N contents were evaluated before and after cultivation. The substrates with 25 and 50% of raw or carbonized rice husk in a mixture with sawdust provided nitrogen and water more adequately to the fungus, improving the fresh mass production, the protein content of mushrooms, and biological efficiency (75–83%) compared to the reference substrate (100% eucalyptus sawdust), without altering the sensory quality. Given the environmental issues caused by carbonization, using raw rice husk in a mixture of up to 50% eucalyptus sawdust is recommended for P. ostreatus production.